A contribution to climate change assessment of storm surges along the coast of Mozambique - Aramuge, Adérito C. F.
About two-third of total population of Mozambique lives along the coast which is 2700 km long. Mozambique is affected by tropical cyclones which are formed in the Indian Ocean, most of them inducing storm surges along the coast. This study presents an analytical model to estimate sea level changes, particularly extreme events (storm surges) from atmospheric pressure and wind data. The meteorological tides, for Maputo tide gauge station, were obtained by applying a low pass filter, with a cut off frequency of 33 hours. The analytical model was validated by comparing the generated meteorological residuals, trough inverted barometer and wind forcing, against the meteorological residual obtained from the tidal gauge. The analysis of the distribution curves of relative and cumulative frequencies, allowed the definition of three classes of storm surges namely: significant, very significant and highly significant for the percentile of 95, 99 and 99.9 respectively. There is a good agreement with a high correlation between the results obtained from the two methods. The alongshore wind, mainly from south or southeast, represents the main contribution for storm surge generation. The analytical model will be used to evaluate changes in the statistical properties of storm surges for future climate change scenarios along the Mozambican coast.